Religious Tolerance of Society in Pati, Central Java: As a Person, Community, and Humanity - Moh Muhtador; Ulya Rofiqoh; Fahrur Rozi (LPPM UIN K.H. Abdurrahman Wahid Pekalongan, 2020)
This article highlight the patterns of tolerance behavior among religious communities in Ngablak village, Cluwak sub-district, Pati district which is depicted in the practice of individual, social, and human life. Individual awareness in a multi-religious and cultural society is the basic capital in constructing human attitudes and behavior. This article aims to determine the characteristics and basis of society in practicing religious tolerance which is manifested in the form of human attitudes and behavior, so that tolerance arises regardless of the background of religion. This article is a field study (field research) with a qualitative approach. The techniques of data collection are by observation, interview, and documentation. Interview was conducted by religious and community leaders in Ngablak village with historical hermeneutic analysis model from Gadamer. The results illustrate that the basic capital of society in building religious tolerance is based on the basis of communal (social) awareness, religious awareness and humanitarian awareness. Religious tolerance cannot be assessed only from the aspect of religion, but history and human values ​​are the supporters in shaping tolerant behavior.